The influence of permafrost and other environmental factors on stream thermal sensitivity across Yukon, Canada - A. J. Szeitz; S. K. Carey (Hydrology and Earth System Sciences)
Thermal sensitivity, defined as the slope of a linear regression between stream and air temperatures, is a useful indicator of the strength of coupling between meteorological forcings and stream temperature or, conversely, of the presence of non-atmospheric thermal influences such as groundwater contributions to streamflow. Furthermore, thermal sensitivity is known to be responsive to environmental change. This study expands the current state of knowledge of stream thermal sensitivity in cold northern regions across catchment scales, investigates the environmental controls of thermal sensitivity across a range of catchment dispositions, and assesses the thermal influence of environmental conditions unique to cold regions, namely permafrost. We conducted a linear regression analysis relating modelled mean daily air and stream temperatures in 57 catchments in Yukon, Canada, with catchment areas ranging from 5.4 to 86 500 km2 and with catchment mean permafrost probabilities ranging from 0.0 to 0.99. Thermal sensitivities obtained from the linear regressions ranged from 0.14 to 0.84 °C °C−1, with a median of 0.56 °C °C−1, and the regression intercepts ranged from −0.07 to 7.60 °C, with the mean regression Nash–Sutcliffe efficiency of 0.81. Thermal sensitivity was positively related to catchment area, land covers representing surface water storage, and streamflow flashiness or a lack of groundwater contributions. The greatest single environmental characteristic explaining the variance in thermal sensitivity was catchment topography (9 % variance explained); however, 39 % of the variance in thermal sensitivity was jointly explained by catchment physiography, land cover, and permafrost presence indicators, suggesting thermal sensitivity is the result of multiple interacting controls. The primary influence of permafrost on thermal sensitivity appeared to be indirect; permafrost controls on catchment properties affecting stream water residence time, subsurface water storage, and subsurface runoff processes provide separate and counteracting effects that are influencing thermal sensitivity.